STATUS OF MUSLIMS MINORITY: A CASE STUDY OF INDIA - Yousaf Tahir; Abdullah; Intizar Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
This research paper, titled "Status of Muslim Minorities: A Case Study of India," aims to understand the economic, political, social, and constitutional status of Muslim minorities in India. Despite the secular nature of the Indian constitution, the majority Hindu population has historically oppressed minorities, particularly Muslims. This research employs a comparative analysis to demonstrate how India’s government apparatus facilitates violations of minority rights. Community violence against Muslims, such as the Gujarat riots during Narendra Modi’s tenure as Chief Minister, exemplifies this oppression. Since Modi’s rise to Prime Minister, radical Hindu hostility towards minorities has intensified. Unilateral laws, such as the Muslim Marriage Act of Triple Talaq and the repeal of Article 370 in Kashmir, further restrict minority rights. Additionally, the Citizenship Amendment Act has been criticized for its discriminatory nature. The liberal philosophy underpinning democratic governance asserts the protection of individual rights; however, significant state-level breaches of minority rights persist in India. This paper corroborates the claim that minority rights violations in India are perpetuated by government mechanisms, reflecting a broader issue of systemic bigotry.